Sistem Digital Pedesaan untuk Optimalisasi Hasil Produk Jagung Kuning di Kecamatan Polongbankeng Utara Kabupaten Takalar - Ummiati Rahmah; Citra Ayni Kamaruddin; Mahmud Mustapa (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
North Polongbangkeng is a part of Takalar Regency where the people grow corn besides rice. However, until now corn plants have only been dried and then sold in the form of shelled seeds, while they can actually be sold in the form of processed food. For this reason, people need to be taught how to process it and then taught how to market it in MSME activities through various digital social media. More specifically, the objectives of this service activity are: 1. Increasing community knowledge in utilizing yellow corn so that it can increase community income. 2. Creating an application that can be used to help increase yellow corn production;; 3 Provide assistance to start-up businesses in the field of yellow corn cultivation; 4. Provide assistance in the use of the Yellow Corn marketing market place via Android Applications and E-Marketing; 5. Diversification of Processed Yellow Corn Products into other processed products and designs. ; and 6. Creation of interactive media and training modules for processing yellow corn has been completed. This service activity received a very good response from the Biralle Kunyi farmer group, as well as North Polongbangkeng State Middle School 4 as the target group. Based on the results of the implementation carried out in these 2 stages, it was able to increase the knowledge and skills of the partner group in applying techniques for processing yellow corn into finished food and was able to market it using social media so that the digitalization system could run as expected in optimizing the marketing of yellow corn processing results.